International Occupational Therapists Continuing Education Needs and Opportunities: A survey - Husny Amerih Ph.D., OTR, ATP (Scholarworks @ WMU, 2013)
Occupational therapists (OTs) are expected to maintain up-to-date knowledge and clinical competence by engaging in continuing professional education (CPE). The objective of this research was to obtain information on CPE needs and opportunities in developed and developing countries. A survey was created and emailed to 520 OTs in various countries, asking questions about CPE requirements, opportunities, and the avenues of CPE available to OTs. One hundred-nineteen OTs from 17 different countries responded. Of the 119 OTs, 28 practice in developing countries and 91 practice in developed countries. Thirty-nine percent of the OTs in developing countries stated that they have certain requirements for CPE. In developed countries 73% of the OTs indicated such requirement were necessary to practice. In developed countries 67% of OTs reported thatCPE was easily available, whereas in developing countries only 25% of OTs reported that CPE was easily available. Therapists in developed countries are more likely to participate in CPE activities, whereas their counterparts in developing countries are not. International OT stakeholders need to explore avenues to makeCPE more available to OTs in developing countries and remote areas.